2011
DOI: 10.5694/j.1326-5377.2011.tb02957.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian general practitioner chlamydia testing rates among young people

Abstract: Objective: To describe the proportion of 16-29-year-olds tested for chlamydia by Australian general practitioners in a 12-month period. Design and setting: Between October 2007 and September 2008, the national chlamydia testing rate in 16-29-year-olds was calculated by dividing the number of Medicare-reimbursed chlamydia tests by two denominators: (i) Medicare-reimbursed GP consultations; and (ii) estimated resident populations adjusted for the proportion who were sexually active. Main outcome measures: GP chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 14 publications
3
81
2
Order By: Relevance
“…Throughout the study period antenatal screening for syphilis and hepatitis B was routine19 21 and so we can presume that women who did not link to a notification did not have these infections. Annual screening for chlamydia was only recommended for young women aged <25 years after 200519 and data suggests that despite this recommendation, testing in this population is still relatively low at <15% 22. Our study found that 1.0% of women having their first birth had a prior chlamydia notification record but when confined to those aged <25 years giving birth after 2005 this increased to 4.6%.…”
Section: Discussionmentioning
confidence: 58%
“…Throughout the study period antenatal screening for syphilis and hepatitis B was routine19 21 and so we can presume that women who did not link to a notification did not have these infections. Annual screening for chlamydia was only recommended for young women aged <25 years after 200519 and data suggests that despite this recommendation, testing in this population is still relatively low at <15% 22. Our study found that 1.0% of women having their first birth had a prior chlamydia notification record but when confined to those aged <25 years giving birth after 2005 this increased to 4.6%.…”
Section: Discussionmentioning
confidence: 58%
“…This is quite different from the ratio seen in the national notification numbers of 1:1.6 (22 703 notifications in young men compared with 37 112 in women in 2010) 14. This imbalance in the notification numbers is most likely attributable to less testing of men and more frequent testing of women (because of the risk of long-term complications) outside sexual health services 7 30…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it provides limited information on patient risk behaviours, an important determinant of infection. Studies have previously demonstrated that notifications are highly correlated with testing,4–6 so when chlamydia testing rates are low, which is the case in many countries including Australia,7 notifications will grossly underestimate the true burden of disease. Conversely, any successful testing initiative has the potential to cause an increase in notifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no routine national surveillance data available to estimate chlamydia testing coverage. However, a recent population-wide Australian study of chlamydia testing based on national health insurance (Medicare) reimbursements for chlamydia tests estimated that in 2007/2008, among 16–29-year-old sexually active women, the proportion who had a test each year was 12.5% 18. Higher testing reported among those participating the 2011 survey and the estimate from the study using 2007/2008 data may be because only Medicare reimbursement data was used, and this does not include chlamydia testing occurring in sexual health clinics or hospitals.…”
Section: Discussionmentioning
confidence: 99%